Wujud Perlindungan Hukum Bagi Wanita Akibat Pembatalan Perkawinan Klandestin - Fi'li, Dimas Auliya Fikri Bil; Soekesi, Titik Soeryati (Universitas Negeri Malang, 2021)
This study analyzed the form of legal protection for women who experienced the annulment of clandestine marriages. This study used an approach in analyzing problems with the approach of legislation and case approach, namely by looking at cases stemming from court rulings and statutory provisions. The results showed that the form of legal protection for women who experienced the annulment of clandestine marriage could be obtained based on Article 136 of the Civil Code, Article 279 paragraph (1), and 263 paragraphs (1) of the article on the Criminal Code. The responsibility of the man who performed clandestine marriage could be in the form of compensation and refund of the circumstances as before by making a statement containing a prohibition to perform the clandestine marriage act in the future.